Pulling away from the trigger: the influences of purpose in life and self-affirmation on decisions to shoot - Burd, Kayla A.; Burrow, Anthony L.; Guyll, Max (Frontiers in Cognition, 2024)
Recent data suggests significant racial disparities in police killings in the United States: Much research finds that Black men are killed by police officers at higher rates than White men, and many individuals killed by police have been unarmed. Towards addressing psychological mechanisms at play in these complicated decision contexts, the current study tested the effectiveness of two writing tasks at reducing the unjustified shooting of unarmed targets using a virtual shooting-decision platform. Participants wrote either about their sense of purpose, selfaffirming values, or a control topic and then played a first-person shooter video game, which randomly presented pictures of Black and White armed and unarmed targets. Participants were instructed not to shoot unarmed targets and to shoot armed targets. Results indicated that relative to controls, writing about either purpose or self-affirming values reduced the probability of shooting unarmed targets, without negatively impacting shooting decision reaction time.